Periodicum biologorum : an interdisciplinary international journal of the Societas Scientarium Naturalium Croatica established 1885 (Croatian Society for Natural Sciences : Ruđer Bošković Institute : LASERplus : Croatian Academy of Sciences and Arts, 2008)
Međunarodni interdisciplinarni časopis koji donosi radove s područja biologije i biomedicine.